2015
DOI: 10.2174/1871526515666150916141907
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin Use in Multi Drug Resistant Uropathogenic <i>Escherichia coli</i>

Abstract: The testing of the newer therapeutic agents like fosfomycin will add on to therapeutics for UTI's.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
3
1
1
Order By: Relevance
“…[12] In another study by Mittal et al ., it was found that fosfomycin was 100% sensitive to uropathogenic E. coli strains. [13] In this present study, 95.18% isolates were susceptible to fosfomycin which is similar to the findings of a study done by Sabharwal and Sharma where it was found that 94.4% of the isolates causing UTI were susceptible to fosfomycin. [14] Khawaja et al .…”
Section: Discussionsupporting
confidence: 90%
“…[12] In another study by Mittal et al ., it was found that fosfomycin was 100% sensitive to uropathogenic E. coli strains. [13] In this present study, 95.18% isolates were susceptible to fosfomycin which is similar to the findings of a study done by Sabharwal and Sharma where it was found that 94.4% of the isolates causing UTI were susceptible to fosfomycin. [14] Khawaja et al .…”
Section: Discussionsupporting
confidence: 90%
“…[14,15] As CLSI does not mention the zone size for Klebsiella sp and Pseudomonas sp, values were interpreted with respect to CLSI interpretative criteria for E. coli. The sensitivity of E coli and Klebsiella sp was more when compared to study done by Zafar et al [13] Same study reports sensitivity of Psudomonas sp to 100% whereas in this study the sensitivity is 41-50%. Review literature suggest inherent and acquired resistant mechanism for Pseudomonas sp which could be responsible forits low sensitivity.…”
Section: Discussioncontrasting
confidence: 56%
“…Similiar to other studies ;E coli is the most common isolate in both the locations in urinary tract infection in this study followed by Klebsiella sp and Pseudomonas. [13] The sensitivity to fosfomycin in E coli isolates was less when compared to other study 85% in OPD isolates and 79% in IPD isolates. [14,15] As CLSI does not mention the zone size for Klebsiella sp and Pseudomonas sp, values were interpreted with respect to CLSI interpretative criteria for E. coli.…”
Section: Discussionmentioning
confidence: 60%
“…60% women will develop an episode of UTIs in their lives and one third of those will have a recurrence within a year. 6 UTIs during pregnancy must be effectively treated to prevent complications associated with it like pyelonephritis, preterm rupture of membrane, preterm labour, chorio-amnionitis, and neonatal septicemia. Repeated urinary tract infection and its treatment with long courses of antibiotic treatment resulted in highly antibiotic resistant bacteria and multi-drug resistant organisms.…”
Section: Discussionmentioning
confidence: 99%